Evaluation of Employee Acceptance of the IMS Application at PT Sarana Utama Adimandiri: TAM Approach - Sancoko, Sancoko; Prayogi, Zahra Shalsabilla; Al Aufa, Badra; Yuliawan, Rahmat (ILKOM Jurnal Ilmiah, 2022)
PT Sarana Utama Adimandiri (SUA) which is engaged in the construction sector implements an IMS application in its purchasing activity. This paper aims at describing the evaluation of employee acceptance of the information system at PT SUA using the Technology Acceptance Model (TAM) approach. TAM has two main variables i.e: perceived usefulness and perceived ease of use which function as independent variables, while the dependent variable is acceptance of IT (integrated management system/IMS applications). The population and sample in this study were all employees of PT SUA, which was used to obtain research data through the distribution of structured questionnaires. The instrument was tested using validity and reliability tests, and data was analyzed by using spearman rank test. This study suggests that there is a strong effect of perceived usefulness and perceived ease of use on acceptance of IT.